Investigation on True Stress-Strain Curves of Flat and Corner Regions of Cold-Formed Section Using 3D Digital Image Correlation Method. (16th December 2019) - Xu, Bo; Xia, Junwu; Ma, Renwei; Wang, Jian; Chen, Xiaomiao; Chang, Hongfei; Zhang, Lihai
Abstract : The true stress-strain curve is the critical method to describe the practical material mechanical performance and the essential precondition to develop the advanced numerical simulation. Experimental, analytical, and numerical procedures were performed in present research to investigate the true stress-strain curves of flat and corner regions of the cold-formed channel section. The coupon tests with the 3D digital image correlation system were conducted on flat and corner specimens to directly obtain the true stress-strain curves. The experimental results indicate that the tensile secondary-hardening phenomenon at the plastic strain stage was observed in the true stress-strain curves of flat coupons, and initial strain hardening behavior was produced in that of corner coupons. Flat region exhibits a significant improvement of true ultimate strength compared to the engineering value. The stress status of the corner region is developed to ultimate strength at the early strain phase and exhibits a slight increase compared with the nominal values at the plastic phase. Cold-rolling action limits the ductility performance of the corner region, which highly restrains the tensile strain hardening at the plastic condition. Thus, the true yielding strength of the corner region is obviously higher, but the true ultimate strength is significantly lower than that of the flat region. Together with the optical measuring results, a trilinear model with two-stage strain hardening and a simplified trilinear models were established for describing the true stress-strain curves of flat and corner regions, respectively. The load-displacement curves from numerical simulations fit very well with those of coupon tests, which validate the reliability of the optic measurement and the dependability of the simplified constitutive models.